A MODEL FOR THE INCORPORATION OF THE TRADITIONAL HEALERS INTO THE NATIONAL HEALTH CARE DELIVERY SYSTEM OF SOUTH AFRICA - Pinkoane, Martha G; Greeff, Minrie; Koen, Magdalena P (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
In South Africa the patient uses both the traditional healers and biomedical personnel’s services out of need for the best healing therapy to fulfil his/ her health needs. Failure of one to yield the expected results leads to the use of the other. This shunting back and forth prompted the researcher to undertake research and formulated a model demonstrating how the traditional healers can be incorporated into the National Health Care Delivery System of South Africa. The research used both qualitative and theory generating designs to attain the set objective. Firstly, a qualitative research design used semi-structured interviews to investigate the perceptions and attitudes of biomedical personnel, traditional healers, patients and policy makers, regarding the process of incorporation. A non-probable purposive voluntary sample was used, selection was done according to a set criteria. Data was analysed and the results of phase one as well as initial literature review were used to construct a conceptual framework for the model. Secondly, a theory generating design was employed using the three phases of Dickoff, James and Wiedenbach (1968:435) to formulate a model which was systematically, logically and consistently conceptualized. In evaluation of this model a predetermined criteria was used. The results showed that the constructed model demonstrated the government formulating policy to legalize traditional healing and affording the traditional healers legal authority to be official partners to the biomedical personnel and avail the quality health care services that fulfils the patients health needs using the primary health care approach.